Automation of commercial account of electric power and increase of its efficiency in distributive networks - Kulyk, V. V.; Pyskliarov, D. S. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The analysis of structure, functions of automated systems of commercial account of electric power (ASCA) in Ukraine, and basic problems which arise on the way of its introduction are considered. The method of determination of optimum sequence of introduction of measuring environment of ASCA, which is based on the method of analysis of Saati hierarchies and game theorises is suggested.